"Our Sister, Mother Earth": Solidarity and Familial Ecology in Laudato Si'. Issue 3 (30th September 2018) - Flores, Nichole M.
Abstract: Laudato si', with its articulation of a familial ecology reflecting Francis's Latin American context, expands the subject of solidarity in Catholic social teaching and thought. Yet, this ecological vision of family fails to attend to the problem of gender subordination latent in Catholic social teaching, including in its approaches to ecology. A vision of solidarity that eradicates gender and ecological subordination must elaborate a familial ecology characterized by both mercy and equality.